N-(4-Methoxy-2-nitrophenyl)-2-(3-methyl-2-oxo-1,2-dihydroquinoxalin-1-yl)acetamide - Mohcine Missioui; Joel T. Mague; Abdulsalam Alsubari; Mhammed Ansar; El Mokhtar Essassi; Youssef Ramli (IUCrData, 2023)
The quinoxaline unit in the title molecule, C18H16N4O5, is slightly puckered [dihedral angle between the rings = 2.07 (12)°] while the whole molecule adopts an L-shaped conformation. Intramolecular hydrogen bonding determines the orientation of the substituted phenyl ring and the amide nitrogen atom is almost planar. The packing in the crystal is governed by C—H...O hydrogen bonds and slipped π-stacking interactions.